2018
DOI: 10.1093/mnras/sty2755
|View full text |Cite
|
Sign up to set email alerts
|

The age of the Galactic stellar halo fromGaiawhite dwarfs

Abstract: We use 156 044 white dwarf candidates with ≥ 5σ significant parallax measurements from the Gaia mission to measure the velocity dispersion of the Galactic disc; 30.8, 23.9, 20.0) km s −1 . We identify 142 objects that are inconsistent with disc membership at the > 5σ level. This is the largest sample of field halo white dwarfs identified to date. We perform a detailed model atmosphere analysis using optical and near-infrared photometry and parallaxes to constrain the mass and cooling age of each white dwarf. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 62 publications
5
58
0
Order By: Relevance
“…Finally, in a recent work, Kilic et al (2018) found 142 halo white dwarf candidates by using Gaia-DR2, out of which 55 are within 100 pc from the Sun. Our algorithm has classified 48 of these objects as halo members.…”
Section: Halo White Dwarf Candidatesmentioning
confidence: 96%
See 4 more Smart Citations
“…Finally, in a recent work, Kilic et al (2018) found 142 halo white dwarf candidates by using Gaia-DR2, out of which 55 are within 100 pc from the Sun. Our algorithm has classified 48 of these objects as halo members.…”
Section: Halo White Dwarf Candidatesmentioning
confidence: 96%
“…However, the recent observed Gaia-DR2 provides a new opportunity in the study of the halo white dwarf population (e.g. Kilic et al 2018). Giving its relevance we devote this section to specifically analyze our halo white dwarf sample.…”
Section: Halo White Dwarf Candidatesmentioning
confidence: 99%
See 3 more Smart Citations